Characterization of maize producing communities in Benin, Ghana, Mali, and Nigeria: West Africa Regional Synthesis Report - Abdoulaye, Tahirou; Bamire, A.S.; Wiredu, A.N.; Baco, M.N.; Fofana, M. (International Institute of Tropical Agriculture, 2011)
Maize is becoming increasingly important as a food security crop in West Africa. However, recurring droughts constitute a continuous challenge to its production. Attempts at addressing the drought problem resulted in the conduct of a participatory community survey of maize production systems with about 20–40% probability of drought risk in four DTMA countries (Bénin Republic, Ghana, Mali, and Nigeria). The project is part of an initiative to develop and disseminate appropriate drought tolerant maize varieties in sub-Saharan Africa. The main objectives of the community survey were to complement household survey data, capture essential qualitative information and data that are difficult to obtain through formal household surveys, and serve as a pilot application for potential expansion through the African region. The survey was conducted in selected communities in two districts with high levels of maize production in each of the DTMA countries. Results show that maize is a major source of food and cash for smallholder farmers. Community members indicated that both positive and negative changes have taken place in the subregion over the 10-year period. Among these, the introduction and adoption of new DT maize varieties have contributed to achieving food security and poverty reduction, as well as enhanced livelihoods for the people. However, appropriate and adequate provision of production inputs (such as fertilizers, good quality seeds, and herbicides) is essential for achieving the optimum yield of DT maize. Constraints to production include long distances to input markets and the consequent high costs of transportation that make it very difficult for most farmers to get access to inputs. Bad road networks, lack of good quality drinking water, and poor health facilities which are common problems faced by farming households are also detrimental to agricultural productivity. Women in the subregion are also committed to farming but constrained by cultural and religious factors. Women have special roles such as in the cultivation of oil seed crops and vegetables on small parcels of land to provide additional income to the household. Thus, making men within farmers’ organizations more aware and appreciative of the value of women’s contributory role in the household will further help to achieve improved food security in the region.